ANALISIS DAYA DUKUNG LINGKUNGAN SEKTOR PERTANIAN BERBASIS PRODUKTIVITAS DI KABUPATEN BANGLI - I Wayan Susanto (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractThe agricultural sector has multi-functions covering the food production or food securityaspects, the increase of farmer welfare or the eradication of poverty, and the preservation oflife environment. The analysis of the supportability of the agriculture sector environment isusing the land supportability approach based on land productivity, which is conducted bycomparing between the supply and demand of land for the population in a certain region.By this method, the general description whether the supportability of land in a certainregion is on surplus or deficit can be understood. The objective of research is to analyze thesupportability of agriculture sector environment based on land productivity. The approachused in this research is quantitative descriptive, while the analysis tools used are: descriptiveanalysis; the analysis against the supply and demand of land based on the calculationmethod suggested by The Decree of The State Minister of Life Environment No.17 of 2009.The Result of this research indicates that the status of environmental supportability ofBangli District on 2011 is shown by land supply (SL) which reaches 167,947.58 Ha andland demand (DL) which attains 74,173.77. These figures are based on the land supportabilityapproach that emphasizes on the land productivity in meeting the demand of biologicalproduct of the region. The comparison between land supply and land demand will facilitatethe environmental supportability status, which is in the surplus category that is SL > DL.